Teaching Methods for Economics and Business Sciences: Book of Abstracts of the 3rd International Scientific Conference - Marina Bajić; admin, (2019)
Educational institutions are important agents of a society’s progress and the wellbeing of its members. Higher education institutions should provide the most sophisticated added value to the personal and professional development of individuals. They need to encourage their employees towards the fulfilment of this responsible mission. The management of these institutions should represent the role model in this regard. Due to globalisation and its economic, social, technological and ecological consequences, the circumstances and requirements of the twenty–first century workplaces have been transformed. Contemporary working environments reward people with inclusive competencies, such as the ability to recognize differing perspectives, to think critically, to be creative, and to collaborate respectfully in different types of social groups. Higher education institutions of economics and business, whose research areas are related to several sub–disciplines of social sciences, are particularly strongly responsible to best motivate and prepare their students for solving complex problems, spanning across multiple domains. This publication comprises summaries of various new perspectives about the challenges of framing higher education learning environments that support the development of requisite twenty–first century competencies of economics and business students.
Keywords: higher education; workplace; competencies; learning environment; social responsibility